METODOLOGI KUALITATIF UNTUK PENELITIAN ILMU AL-QUR’AN DAN TAFSIR: TELAAN KONSEPTUAL DAN PRAKTIS - Muhamad Rezi; Farit Afrizal; Syed Mohamad Zainudin Bichk Koyak (LP2M Universitas PTIQ Jakarta, 2025)
The Qur'an and Tafsir have a broad scope of study. Studying the Qur'an and Tafsir can be classified as interdisciplinary and multidisciplinary. Besides interpretation and understanding, the methods used in studying the Qur'an and Tafsir are also evolving. Those who focus solely on the text of the Qur'an move towards interpretive texts to analyze the Qur'an and develop realistic perceptions. Known methods include Tafsir Maudhu'iy, Tahliliy, Muqâran, and Ijmâliy, which have been designed with both quantitative and qualitative approaches. A wide range of data sources from various scientific backgrounds has led to the development of diverse data analysis techniques. This article aims to integrate common qualitative theories used in other social sciences, such as social studies and education, with the Qur'an and Tafsir, which also belong to the social sciences field. The author endeavors to clarify several theoretical explanations related to integrative and qualitative research. Using descriptive analysis, this article introduces research tools, data collection techniques, and how to develop a research background on the Qur'an and Tafsir from a qualitative research perspective.